2017
DOI: 10.3892/or.2017.5751
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA XIST interacts with miR-140 to modulate lung cancer growth by targeting iASPP

Abstract: X-inactive specific transcript (XIST), one of the first found cancer-associated long non-coding RNAs (lncRNAs), is involved in the development and progression of many types of tumors. Aberrant expression of XIST has been observed in hepatocellular carcinoma, cervical, breast, ovarian and colorectal cancer. However, the exact effects and molecular mechanisms of XIST in lung cancer progression are still unknown to date. In the present study, we investigated the role of XIST in human lung cancer cell lines and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 39 publications
4
39
0
Order By: Relevance
“…Interestingly, numerous research reported that as an oncogenic lncRNA, XIST promoted tumor proliferation and inhibited tumor apoptosis. Tang et al (2017) suggested that XIST promoted the proliferation and metastasis of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, numerous research reported that as an oncogenic lncRNA, XIST promoted tumor proliferation and inhibited tumor apoptosis. Tang et al (2017) suggested that XIST promoted the proliferation and metastasis of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…XIST can promote esophageal squamous cell carcinoma via regulating miR‐101/EZH2 axis (Wu et al, ). It is reported that XIST serve as an oncogenic lncRNA, which can promote the proliferation and metastasis of lung cancer via sponging miR‐140 (Tang et al, ). XIST can lead to neuronal apoptosis by inhibiting AKT phosphorylation and it is down‐regulated by miR‐494 in rat spinal cord injury (Gu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Since a lot of classic signal pathways that are regulated by miRNAs, such as JNK [83], Wnt/β-catenin signaling pathway [84], or MAPK [85], also influence the expression of several lncRNAs in lung cancer tissues, it is safe to presume that some of the classic tumor-associated pathways are coregulated by lncRNAs and miRNAs. For example, miR-21 influences GAS5′s regulation of NSCLC cisplatin sensitivity through the PTEN pathway [86], and lncRNA-XIST can promote proliferation and metastases in lung cancer via miR-140 regulation of the p53 (inhibitor of apoptosis-stimulating protein of p53-iASPP) pathway [87].…”
Section: Long Noncoding Rnasmentioning
confidence: 99%
“…New target therapies, such as EGFR-activating tyrosine kinase inhibitors (TKI), confirmed their superiority to chemotherapy and research focused especially on EGFR-activating mutations and abnormal gene fusion between echinoderm microtubule-associated protein-like 4 and anaplastic lymphoma kinase (EML4-ALK) [24,25,[87][88][89]. In order to detect the presence of mutations, repeated invasive examinations are required, which can cause discomfort to the patient.…”
Section: Liquid Biopsy In Lung Cancermentioning
confidence: 99%